Blood Indices Replace Upper Gastrointestinal Endoscopy for the Prediction of Clinically Significant Esophageal Varices in Liver Cirrhosis - Venkatakrishna Sankapithlu; Gnanendra Mariyanna; Kiran Shankar; Sanjay Kumar Hassan Raghunath; Kavya Seenahalli Thimmaiah (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2021)
Background and aim: Anticipating the existence of esophageal varices (EVs) by non-intrusive methods in cirrhotic may build consistency and limit the presentation of upper gastrointestinal endoscopy (UGIE) to those individuals with a high likelihood of having EVs. Prophecy of EVs utilizing simple blood indices and also for estimation of clinically important large esophageal varices (LEVs).Materials and methods: A cross-sectional experimental examination was done on 107 cirrhotic enlisted sequentially. Platelet count (PC), the ratio of aspartate aminotransferase to alanine aminotransferase (the AST/ALT ratio or AAR), AST-platelet-ratio index (APRI), Fib-4, and King's Score were determined and linked with UGIE discoveries taken as the best quality level. The execution manifested affectability, particularity, positive and negative prescient values (PPV, NPV), and area under the curve (AUC).Results: Middle age 44 years, male (90%), and etiology-ethanol (87%). 60/107 had LEVs. For anticipating LEVs, PC at cutoff esteem < 1.5 lakhs c/mm3 exhibited affectability 66.7%; particularity 44.7%, PPV 60.6%, NPV 51.2%, and AUC 0.621. AAR for estimation of LEVs at cutoff esteem 1, showed affectability 93.3%, particularity 42.1%, PPV 54.9%, NPV 20% and AUC 0.638. Lie 4 for expectation of LEVs at cutoff esteem 3.5, showed affectability 80%, and particularity 31.9%, PPV 60%, NPV 55.6% and AUC 0.614.Conclusion: PC, AAR, and FIB-4 had simple demonstrative precision for LEVs in cirrhosis. They recognized the subcategory that requires UGIE for the preventive administration of EVs. Generally, basic blood lists probably will not have the option to substitute the efficacy of UGIE for the finding of EVs in cirrhosis.